IKONOGRAFI ARCA KARIVARADA GAJENDRA MOKSA DALAM KONTEKS MASYARAKAT MUSLIM DI DESA BROKOH - Hidayat, Manarul (Bapelitbang Kabupaten Batang, 2024)
This study examines the iconography of the Karivarada Gajendra Moksa Statue located in Brokoh Village, Batang Regency, within the context of the local Muslim community. The statue represents Lord Vishnu rescuing Gajendra the Elephant, symbolizing the liberation of the soul bound by worldly life. Brokoh Village, whose population is predominantly Muslim, demonstrates an intriguing engagement with this Hindu statue as part of the local cultural heritage. This study employs a qualitative method with an iconographic approach, incorporating field observations, literature reviews, and ethnographic interviews with the local community. The findings reveal that the residents of Brokoh generally regard the statue as a historical monument rather than a religious object. The community’s neutral response to the statue reflects a strong sense of cultural tolerance. This study contributes to a deeper understanding of the integration of Hindu symbolism into Muslim communities, while enriching the discourse on the preservation of interreligious cultural heritage in Indonesia. The Karivarada Gajendra Moksa Statue in Brokoh Village stands as an important example of how religious symbols from the past can coexist within a predominantly Muslim society, not creating social tension but instead enriching the local cultural identity.